Die strafrechtliche Behandlung gefährlicher Straftäter Ein deutsch-koreanischer Vergleich - Park, Sang-Min (Universitätsverlag Göttingen, 2015)
The thesis analyzes a treatment of dangerous criminals on society with viewpoint of comparative criminal law in Germany and South Korea. In particular, with a focus on "preventive detention" as a "measure of improving and security", at first, basic theory of the Measure of Improving and Security is referred for the analysis of Preventive Detention. At the end of the thesis possible alternatives to Preventive Detention are reviewed. As a result, duality of the criminal law and Measure of Improving and Security will have to be acceptable to the Criminal Code, but the focus of the criminal treatment of dangerous criminals should also be successful treatment and re-socialization, alternatives that do not deprive of freedom emphasized to hold a dominant position.